EARLY OUTCOME OF SURGICAL VENTRICULAR SEPTAL DEFECT CLOSURE IN KURDISTAN: A MULTICENTER STUDY - Ahmed, Omid Mohammed Ahmed; Salih, Aso Faeq Salih; Mahmood, Nadine Abulrazzak Mahmood Nadine Abulrazzak (Journal of Sulaimani Medical College, 2024)
Background Ventricular septal defect (VSD) is the most frequently occurring congenital heart defect (CHD). However, outcomes vary after surgical closure, and no consensus exists on risk factors for unfavorable outcomes. Objectives The objective was to assess the short-term outcomes of surgical closure of VSD in patients aged 18 or younger. Materials and Methods A retrospective case series study was conducted in three tertiary centers in the Iraqi Kurdistan region. among patients under 18 years of age who underwent VSD closure as their primary surgery between June 2021 and December 2022. Results The study involved 84 patients who had VSD surgically closed. Adverse events occurred in 58.3% of cases, with a 2.4% mortality rate. Mean age and weight were 57.3 months and 16.2 Kg respectively. Perimembranous VSD was the most common type (72.6%). The most common indications for closure were left ventricular (LV) dilation, pulmonary hypertension, and aortic regurgitation (AR). The mean intensive care unit (ICU) stay duration was 34.7 hours, and the mean hospital stay duration was 6.9 days. Low-weight, younger age, and syndromic children had longer ICU and hospital stays (p<0.001). Conclusion infants under the age of one year, weighing less than ten kilograms, along with patients suffering from pulmonary artery hypertension and syndromic conditions, are at a greater risk of experiencing adverse outcomes. However, in our specific context, it is possible to perform Surgical VSD closure with an acceptable level of mortality and morbidity
Keywords: Congenital heart surgery Surgical repair outcome Ventricular septal defects